Semiotics: The Connotatives Signified (Myth) on Several News Headlines About Terror Cases Indicating Islamophobia - Artha Nur Restia Panji (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2020)
In the last couple of years the increasing cases of violence and terror appears to be the most common headlines in the media around the world.  Media platforms seem to use the news of violence and terror as their strategy to attract readers, in which some news appears to be provocative. The terms used in the media also tend to be exaggerative, which mostly beyond the actual context of the cases. Moreover, the media platforms appears to be trapped in Islamophobia attitude, as they tend to use the term ‘terror’ identical to cases of crimes perpetrated only by Muslims. The term ‘terror’ is hardly used in cases of crimes involving non-Muslims, instead the news platform will use such more neutral terms as ‘shooting’ and ‘stabbing.’ This article examines the connotative meaning of the different terminologies used to describe similar cases in the media headline. In the perspective to Critical Discourse Analysis theory, a discourse brought up by news headline is not merely word choices as it expresses more than just linguistic aspect. In fact, it shapes the way the readers portrayed the actual cases, while the terms used in the news headline appear to significantly contribute to the development of certain ideology brought by the media platforms.[Dalam beberapa tahun terakhir, meningkatnya kasus kekerasan dan teror menjadi berita utama dan lumrah di media di seluruh dunia. Platform media terlihat menyiarkan berita kekerasan dan teror sebagai strategi mereka untuk menarik khalayak untuk membaca yang mana beberapa berita tersebut cenderung lebih provokatif. Istilah-istilah yang digunakan dalam berita itu juga cenderung berlebihan yang justru berada di luar konteks kasus yang sebenarnya. Selain itu, platform media juga terjebak dalam sikap Islamofobia, dengan cenderung menggunakan istilah ‘teror’ yang identik dengan kasus-kasus kejahatan yang mengarah pada tindakan umat Islam. Istilah ‘teror’ justru jarang digunakan dalam kasus-kasus kejahatan yang melibatkan non-muslim, dan sebaliknya, platform berita itu akan menggunakan istilah yang lebih netral seperti ‘penembakan’ dan ‘penusukan’. Artikel ini mengkaji makna konotatif dari istilah-istilah yang digunakan media platform untuk menyampaikan kasus-kasus tersebut dalam tajuk media. Dalam perspektif teori Analisis Wacana Kritis, sebuah wacana yang diangkat oleh tajuk berita tidak hanya berupa pilihan kata sebab dibalik kata itu terdapat ungkapan yang lebih dari sekedar aspek linguistiknya saja. Bahkan, kata-kata itu turut menbentuk cara pembaca memahami dan menggambarkan kasus-kasus tersebut, padahal istilah-istilah yang digunakan oleh media itu nyatanya memiliki peran penting pada pertumbuhan ideologi tertentu yang dibawa oleh media platform tersebut.]